A Model for Learning Disorders based on the Relationship with Parents and Perfectionism - Tavasolizadeh, Rahil; Hosseini, Saeedeh Al-sadat; Amiri, Hassan; Arefi, Mokhtar (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to determine the learning disorder model based on the relationship with parents and perfectionism. Methods: The research was applied in terms of purpose and had descriptive survey and correlational type in terms of data collection method, and its statistical population consisted of all fifth and sixth-grade female students in Kermanshah in the academic year of 2020-2021. Furthermore, 270 female students and their parents were selected as statistical samples using the convenience sampling method and they answered the learning disability questionnaire by Wilcott et al. (2011), the parent-child relationship quality questionnaire by Fine et al. (1983), and the Multidimensional Perfectionism Scale by Hewitt and Flett (1991). Results: There were significant correlations (P=0.05) between positive affect, identification with parents, trust, anger, self-oriented perfectionism, other-oriented perfectionism, and society-oriented perfectionism with learning disorders (P=0.05). Furthermore, the multiple correlation coefficient between perfectionism and the quality of the parent-child relationship with learning disorder was equal to R=0.462, and the coefficient of determination was equal to R2=0.213. Moreover, 21.3% of the variance of learning disorders could be explained by perfectionism and the quality of the child-parent relationship. Conclusion: The relationship with parents and also perfectionism contributed to the prediction of learning disorders.